LEC-TMAC: Improving Energy Consumption & Latency in TMAC Protocol for Wireless Body Area Network - Shravan Kumar Upadhayay; Mansi Gupta (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
The most common protocols for Wireless Body Area Network (WBAN) like TMAC, ZigBeeMAC, Baseline MAC protocol .In this paper, evaluating the effects of LEC-TMAC Protocol wireless body area network basis of Latency and energy consumption. This analysis is important in point of view that the varying requirement of WBAN according to varying conditions. In LEC-TMAC, the application packet rate of nodes a considerable effect is observed on latency and energy consumption for MAC protocols that is presented in the paper. As a conclusion, we invoke a number of new research challenges with regard to prospects of Wireless body area network and other issues.